2017
DOI: 10.1542/hpeds.2016-0127
|View full text |Cite
|
Sign up to set email alerts
|

Ordering Interruptions in a Tertiary Care Center: A Prospective Observational Study

Abstract: Residents and physician assistants are interrupted at a rate of 57 interruptions per 100 orders placed. This may contribute to ordering errors and worsen patient safety. Efforts should be made to decrease interruptions during the ordering process and track their effects on medication errors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…In the prospective observational study conducted by Dadlez et al 27 1-hour-long structured observations on morning rounds and a ernoons and evenings in the resident workroom. The primary outcome was the number of interruptions per 100 orders placed by residents and physician assistants.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the prospective observational study conducted by Dadlez et al 27 1-hour-long structured observations on morning rounds and a ernoons and evenings in the resident workroom. The primary outcome was the number of interruptions per 100 orders placed by residents and physician assistants.…”
Section: Resultsmentioning
confidence: 99%
“…Gill et al (Australia, 2011) 26 don't specify the type of factors causing interruptions, asserting that they a ect the application of the protocol of the correct management of the therapy. Dadlez et al (USA, 2017) 27 found that the majority of interruptions were in person or by phone and overall, the individuals initiating the interruption most commonly were nurses, in addition to the fact that the vast majority of these interruptions were non-urgent. They developed various interventions, including marked no-interruption zones in medication preparation areas, having nurses wear a visible symbol to indicate the process of medication administration time, designation of speci c protected medication rounding time, and scripting for nurses to defer interruptions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study explored interruptions in various contexts of health care, mainly in the activity of preparation and administration of medicines (42) . It is one of the most complex and critical activities performed by nursing professionals.…”
Section: Discussionmentioning
confidence: 99%
“…8 In order to accommodate interruptions, physicians often employ task switching, which occurs when the interrupted person stops their current task, engages with a new task, and then subsequently returns to the initial task. 9,10 It is well known that task switching can degrade performance and increase the rate of errors, [9][10][11][12][13] but it also increases cognitive load and therefore can interfere with learning. [14][15][16] Classroom investigators have shown that text messaging during lectures degrades recall and learning, and that frequent interruptions can disrupt encoding of new material into long-term memory.…”
Section: Introductionmentioning
confidence: 99%